SUCCES FACTORS AND OBSTACLES IN IMPLEMENTING INTERCOMMUNITY DEVELOPMENT PROJECT - Nicoleta LAȘAN (Annals of the University of Oradea: Economic Science)
The present paper aims to determine the success factors and obstacles in implementing intercommunity development projects through associations of public authorities. Intercommunity cooperation institutionalizes the cooperation between two or more local public authorities, allowing them to jointly administer certain important services, and in recent years this type of cooperation has been on an upward trend in Europe as well as in Romania. The study is empirical and the research is quantitative, the results reflecting the responses to a questionnaire applied to public authorities members of an intercommunity development association. The first part of the study focuses on literature review, most relevant researches in the field being presented as well as the differences between the existing studies and the present one. The study continues with the analysis of the main success factors and barriers in implementing intercommunity development projects based on the results obtained from the questionnaire applied. The results of the questionnaire were interpreted using the Excel analysis tool. In the end, the main conclusions are drawn, as well as possible future research directions that can complement the present study. The results of the research are useful for improving intercommunity development projects on all levels: preparation, management, communication, implementation, results and final beneficiaries, and to overcome obstacles that have been identified.